Educação Física escolar e praxiologia motriz: aproximações iniciais a partir de uma proposta de formação continuada - Zaghi, Flavio Henrique Lara da Silveira (Universidade Federal de São Carlos, 2022)
The present study sought to establish some important and necessary themes for school physical education, they are: physical education, sport, game, school, teacher training and motor praxiology. From the 1980s onwards, school physical education went through moments of great uncertainty and crises, providing some reflections, studies and research that contributed to the paradigmatic change experienced in this historical period. The great split consisted in overcoming the biological and sports conception of physical fitness that permeated the area. In this wake, physical education gained pedagogical contours arising mainly from critical theories of education. Therefore, as a curricular component, physical education began to appear in official documents produced at the national level. The most recent guiding document is the National Curricular Common Base. In this document, one of the concepts that underpins the Sport thematic unit is “internal organization”. We understand that, in general terms, this concept comes, to a certain extent, from the theory nicknamed by French professor Pierre Parlebas, the Theory of Motive Action. In this sense, the research problem is based on what are the initial implications of a continuing education course for physical education teachers, guided by the theoretical bases of motor praxiology, for the ways of thinking about the teaching of sport and games at school? In the search to answer the research problem question, we arrived at the objective that is to reveal the evidence of praxeological elements constructed by teachers of Physical Education participating in a continuing education. In this way, a continuing education course was proposed, based on the members of the knowledge base, specifically content knowledge and pedagogical content knowledge, as well as the relationship of knowledge related to the experience of teachers. We understand, therefore, that the continuing education of teachers must overcome the hegemonic model of technical-instrumental rationality, seeking a horizontal relationship between the effective participants of the training. The methodology used was based on qualitative research, which allows the researcher to establish a close relationship between the researcher and the subjects, as well as with the environment/research field. We also used, in this study, the approach of the pedagogical intervention research, which proposes investigations that contemplate the planning actions and the implementation of pedagogical interventions. Eight physical education teachers from the public network of a city in the interior of the state of São Paulo participated in this study. With the means of obtaining data, eight training meetings were held over three months. Another route used was the semi-structured interviews with the teachers participating in the course. Data collection took place through the transcription of training meetings and in-depth interviews. Data analysis was supported by the content analysis technique that allows categorizing and classifying findings into categories. After transcribing the reports and analyzing the data, we arrived at three main categories, namely: the first one dealt with the elements relevant to the training course, the second block of analysis was based on the concepts studied in the training course and, finally, the third block comprehended the relationship between what and how to teach in school physical education through praxeological concepts. In general terms, the continuing education course provided the exchange of experiences that were fundamental for the construction of knowledge. Participants also indicated difficulty in understanding the concepts of the theory studied, however they reported that the deepening of many concepts allowed an awareness and rationalization of pedagogical practice. In general terms, it is noticeable that the praxiological elements contributed significantly to the process of planning, systematizing and teaching sports.
School Physical education and motor praxiology: initial approaches from a continuing training proposal
Keywords: Educação física escolar; Formação continuada de professores; Praxiologia motriz; School physical education; Teacher training; Motor praxiology; CIENCIAS HUMANAS::EDUCACAO